(untitled) (Літератури світу: поетика, ментальність і духовність, 2015)
The aim of the paper is to draw attention of Ukrainian scholars to the oeuvre of one of the most prolific and accomplished contemporary American writers – Percival Everett, focusing on his satirical novel «American Desert». The novel explores many painful issues of contemporary American society, in particular – the question of true religious belief and spirituality and exponential religiosity and spirituality. The paper shows that the grotesque depiction of society defects and vices makes the reader think about the true values in life.